Discussion Method as an Effort to Improve Student Learning Outcomes in Fiqh Learning: A Classroom Action Research - Srianti, Dewi (MANDAILING GLOBAL EDUKASIA, 2024)
Learning methods are one aspect that must be considered by every teacher in an effort to achieve learning objectives. To a certain extent, learning methods can create more meaningful learning. This study aims to improve student learning outcomes in fiqh learning by using the discussion method. This study is a classroom action research with the Kemmis & Mc Taggart design which uses four steps, namely planning, action, observation and reflection. The subjects of this study were students of state junior high school 3 Lima Puluh Kota. The research data were obtained using observation and test techniques. The data obtained were then analyzed using descriptive statistical techniques. The results of the study indicate that the discussion method can improve student learning outcomes in fiqh learning. This can be seen from the increase in learning outcomes in each cycle. Therefore, the discussion method can be used as one of the methods in fiqh learning.